Niches depicting figures of Shiva, Ganesha and a goddess - Temples of India Project Team (Jio Institute, 2024)
A closer view of the lintel of the dvarashakha (door jamb) of the mulaprasada (main shrine) of the Neelkanth Mahadev Temple. This lintel has five rathikas (small niches) with depictions of Shiva at the centre, flanked by Ganesha on the right and goddess on the left. The rathikas in the furthest corners are not easily accessible. Since the central rathika of the lintel has a Shiva image, the lalatabimba (key stone of the lintel) has an image of Nandi.